Risdiplam treatment has not led to retinal toxicity in patients with spinal muscular atrophy. Issue 1 (24th November 2020) - Sergott, Robert C.; Amorelli, Giulia M.; Baranello, Giovanni; Barreau, Emmanuel; Beres, Shannon; Kane, Steven; Mercuri, Eugenio; Orazi, Lorenzo; SantaMaria, Melissa; Tremolada, Gemma; Santarsiero, Diletta; Waskowska, Agnieszka; et al.
Abstract: Objective: Evaluation of ophthalmologic safety with focus on retinal safety in patients with spinal muscular atrophy (SMA) treated with risdiplam (EVRYSDI®), a survival of motor neuron 2 splicing modifier associated with retinal toxicity in monkeys. Risdiplam was approved recently for the treatment of patients with SMA, aged ≥ 2 months in the United States, and is currently under Health Authority review in the EU. Methods: Subjects included patients with SMA aged 2 months–60 years enrolled in the FIREFISH, SUNFISH, and JEWELFISH clinical trials for risdiplam. Ophthalmologic assessments, including functional assessments (age‐appropriate visual acuity and visual field) and imaging (spectral domain optical coherence tomography [SD‐OCT], fundus photography, and fundus autofluorescence [FAF]), were conducted at baseline and every 2–6 months depending on study and assessment. SD‐OCT, FAF, fundus photography, and threshold perimetry were evaluated by an independent, masked reading center. Adverse events (AEs) were reported throughout the study. Results: A total of 245 patients receiving risdiplam were assessed. Comprehensive, high‐quality, ophthalmologic monitoring assessing retinal structure and visual function showed no retinal structural or functional changes. In the youngest patients, SD‐OCT findings of normal retinal maturation were observed. AEs involving eye disorders were not suggestive of risdiplam‐induced toxicity and resolved with ongoing treatment. Interpretation: Extensive ophthalmologic monitoring conducted in studies in patients with SMA confirmed that risdiplam does not induce ophthalmologic toxicity in pediatric or adult patients with SMA at the therapeutic dose. These results suggest that safety ophthalmologic monitoring is not needed in patients receiving risdiplam, as also reflected in the United States Prescribing Information for risdiplam.